(untitled) (Journal of Information Technologies in Education (ITE), 2015)
The article substantiates the effectiveness of learning technologies using Moodle in shaping personality traits of future ecologists during natural-scientific study: as the result of the analysis of research, it was found that Moodle has significant opportunities for the development of individual psychological characteristics that are important both for the future ecologists, and for a modern specialist in general; describes the structure of e-courses of natural sciences that were developed and are used in Khmelnitsky National University, and proved that the personality traits formation of the future ecologists is provided by all the courses resources – informational educational materials, practical and laboratory work, the recommendations for implementing the independent work, academic and control tests, interactive elements of the courses etc. The results of the experimental research on implementation of technology using Moodle in the process of naturalscientific study of future ecologists were analysed; the effectiveness of using Moodle in shaping the personality traits of the future ecologists was experimentally confirmed: such traits as the capacity for self-development and self-education, creativity, reflection, focus on individual success / failure avoidance and it was recommended to use educational technologies using Moodle to improve natural-scientific study of future ecologists in higher education institutions.